Effect of Exogenous and Endogenous Glucocorticoids on the Spermatogenesis of Albino Rats; A Comparative Study - Uzma Hameed; Sadia Iqbal; Fatima Rehman; Aisha Hassan; Ayesha Majeed Memon; Sumera Mustafa (KARACHI MEDICAL AND DENTAL COLLEGE, 2020)
Objective: The objective of the present study was to compare the earlier possible effects of exogenous and endogenous glucocorticoids on the spermatogenesis of albino rats. Methods: This comparative study was conducted at Baqai Medical University in the Department of Anatomy from June till July 2016. Total of 96 adult Sprague rats were used in this study obtained from Agha Khan University; their ages were between 10-12 weeks and their weight ranged between 180-200 gms. Exogenous glucocorticoids were given through intraperitoneal route (i.p. route) at the dose of 1.2 mg/kg/body weight and for endogenous production of cortisol, they were kept in a plastic box daily which was thermostatically maintained at 44º C for 1 hour. They were divided into three main groups and the main group was further categorized into subgroups according to their number of days. The three main groups were; A (control), B (exogenous glucocorticoid), and C (endogenous glucocorticoid). They were sacrificed at the end of the experiment, testes were removed and the effects of exogenous and endogenous glucocorticoids on the spermatogenesis were observed under the light microscope in H&E and PAS stained sections. Results: Spermatogenesis was assessed by Johnsons scoring which ranges from 10 to 1. In the control group, complete spermatogenesis was observed with a Johnson's score of 10 while in group B and C scores were between 10-2 and 10-3, respectively. Conclusion: From the present study, we conclude that exogenous glucocorticoids cause earlier damage and effects all stages of spermatogenesis with decreased production of quality sperms. This animal study will help to decrease the infertility rate due to excessive and unnecessary use of glucocorticoids especially in the early years of life and by taking preventive measures when exposed to high temperatures.